2009
DOI: 10.3766/jaaa.20.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Evoked Myogenic Potential (VEMP) Testing: Normative Threshold Response Curves and Effects of Age

Abstract: Background-Vestibular Evoked Myogenic Potential (VEMP) testing has gained increased interest in the diagnosis of a variety of vestibular etiologies. Comparisons of P13 / N23 latency, amplitude and threshold response curves have been used to compare pathologic groups to normal controls. Appropriate characterization of these etiologies requires normative data across the frequency spectrum and age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
68
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 29 publications
15
68
0
5
Order By: Relevance
“…Analyzing the male and female populations, we did not find significant differences for p13 and n23 absolute latencies between the right and left ears, which corroborates previous studies, using stimuli at the frequencies of 1,000 Hz 18 , 500 Hz 21 and for click stimuli 22,23 . In the sample studied, we did not find differences between the genders, for all VEMP parameters, as per seen in a previous study 24 , for tone burst stimuli of 250, 500, 750 and 1000 Hz. In other studies (500 Hz tone bursts), there were no reports of changes in VEMP for the absolute latency; nonetheless, we noticed differences in the p13-n23 22,25 amplitudes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Analyzing the male and female populations, we did not find significant differences for p13 and n23 absolute latencies between the right and left ears, which corroborates previous studies, using stimuli at the frequencies of 1,000 Hz 18 , 500 Hz 21 and for click stimuli 22,23 . In the sample studied, we did not find differences between the genders, for all VEMP parameters, as per seen in a previous study 24 , for tone burst stimuli of 250, 500, 750 and 1000 Hz. In other studies (500 Hz tone bursts), there were no reports of changes in VEMP for the absolute latency; nonetheless, we noticed differences in the p13-n23 22,25 amplitudes.…”
Section: Discussionsupporting
confidence: 87%
“…In our data, we noticed a lower p13 value, the most used parameter in the VEMP analysis 24,27 . For the amplitude parameter analysis, we chose to calculate the asymmetry index, because the absolute amplitude values have very little intra and intersubject reproducibility and are dependent on factors such as age, intensity and frequency of the stimulus and muscle tonus contraction.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies have shown that both short tone bursts (STBs) and clicks can evoke myogenic potentials [9], but some studies described that VEMP response is better to clicks than STBs [10], while others have shown that 500 and 750 Hz STBs evoked larger amplitudes compared to 250 Hz STBs and clicks [11,12]. Although the reliability of STB-induced VEMPs has been investigated [13][14][15][16][17], a comparative study of individual responses to STB-and clicks-induced VEMPs in a group of healthy subjects has not been carried out and there is no rationale for using either click or STB.…”
Section: Introductionmentioning
confidence: 98%
“…The bilateral cVEMP response rates of healthy adults to 500-and 1000-Hz TB stimuli are reported to be 94% and 89%, respectively, depending on the stimulus frequency [8] .…”
Section: Discussionmentioning
confidence: 99%